2023
DOI: 10.3390/jcm12113856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Masticatory Muscle Activity and Rhythmic Jaw Movements Evoked by Electrical Stimulation of Different Cortical Masticatory Areas

Ruixin Li,
Chiho Kato,
Akiyo Fujita
et al.

Abstract: This study investigates rhythmic jaw movement (RJM) patterns and masticatory muscle activities during electrical stimulation in two cortical masticatory areas in obese male Zucker rats (OZRs), compared to their counterparts—lean male Zucker rats (LZRs) (seven each). At the age of 10 weeks, electromyographic (EMG) activity of the right anterior digastric muscle (RAD) and masseter muscles, and RJMs were recorded during repetitive intracortical micro-stimulation in the left anterior and posterior parts of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The duration of wearing a retainer was not a significant contributor; however, estimates suggested that wearing retainers for more than four years decreased associations with jaw clicking. A recent study suggested that obesity can significantly impede physiological masticatory function and affect jaw movement [26]. Therefore, BMI and maximum mouth opening were included in the current model to account for anatomical variations.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of wearing a retainer was not a significant contributor; however, estimates suggested that wearing retainers for more than four years decreased associations with jaw clicking. A recent study suggested that obesity can significantly impede physiological masticatory function and affect jaw movement [26]. Therefore, BMI and maximum mouth opening were included in the current model to account for anatomical variations.…”
Section: Resultsmentioning
confidence: 99%